Conceptual Bases of Realization of the Sound Image - Khusanov Shoislom Shoolimogli (International Journal of Advanced Science and Technology, 2020)
This article discusses the physical nature of sound, the sound range of frequencies, the dynamic range of hearing, real sound, the spectra of sound vibrations and timbre. It also describes the spatial perception of sound and sound indoors, examines the acoustic processing of the studios and the requirements for their parameters. The article also covers material on mechanical and photographic systems of sound recording, magnetic sound recording.It also discloses technologies for multi-track recording, digital sound recording and signal processing, digital sound recording on various storage media. Especially in it, each stage of this process is examined in detail: from the signal to the microphone, to the processing of the final digital series. Adescriptionofthevocationaltrainingofphonogramsusedforthisequipmentandmethodsofsubjectiveassessmentofrecordingqualityisgiven.An example of amateur recording a music program on a compact disc using a personal computer is shown. A detailed analysis of the causes of deficiencies associated with both the CD itself and the reader, which can affect the quality of the reproduced sound, is carried out.